(untitled) (Physical Education, Health and Social Sciences, 2025)
The development of safety assessment for active pharmaceutical ingredients and their excipient is vital to their regulatory clearance for human use. The acute oral and dermal toxicity studies of a copolymeric hydrogel synthesized from the polymerization of Salvia hispanica seed mucilage and acrylamide were established by following the protocols and guidelines 420 and 402 of the OECD. The ocular toxicity and eye irritation tests were performed and analyzed through the Draize scale. For toxicity studies, the rabbit was used as model animal and were categorized into four distinct groups. The animals (rabbits) in group A1 were not treated with copolymeric hydrogel and served as control. While the animals of other groups, i.e., A2, A3, and A4 were administered copolymeric hydrogel dose of 0.05, 0.3, and 2 g/kg of the bodyweight, and served as the treated groups. All animals were observed for their behavior, food consumption, water intake, allergic reactions, mortality rate, and any other side effects for 14 days. All the observed animals survived without any significant behavioral and physiological abnormalities. The biochemical analysis and hematological tests were assessed after 14 days in both animal groups, control and treated, which were consistent and comparable. The major internal organs of animals were exercised to determine the weight of the organs. The cumulative findings from acute oral and dermal toxicity studies indicated that the synthesized copolymeric hydrogel is safe and non-toxic when orally administered or directly applied to the skin surface. Consequently, it can be demonstrated as potential excipient for pharmaceutical drug delivery systems and wound dressing applications.